Study on the Characteristics of Near-shore Waves in the Typical Section of the Three Gorges Reservoir Area: A Case Study of Daning River - FU Xuhui; WANG Shuo; TANG Dingdan; SONG Yuanyuan; WANG Yunyou; ZHANG Yixin; YANG Ming (Renmin Zhujiang, 2020)
This paper conducts field observations of near-shore waves in the Dachang section of theDaning River Basin, a tributary of the Three Gorges Reservoir area, observes the heights of near-shorewind and ship waves at a water level of 160 m in the reservoir area by high-definitiondigital cameras and rulers, carries out the parameter test, Weibull distribution fitting andgoodness-of-fit test on more than 1 000 sets of measured wave height data by Minitab software, andanalyzes the spatial and frequency characteristics of near-shore waves. The results show that: 1)The height of the waves caused by wind varies within a range of 0~5 cm, and the distribution ofwaves is uniform; 2) The height of the ship waves varies within a range of 1~12 cm; 3) The measuredeffective wave heights of the four groups of different banks are fit well with the Weibulldistribution. The height of near-shore ship waves is mainly 6~10 cm, accounting for 90%; while thatof near-shore wind waves is mainly 2~4 cm, accounting for 85%. The results provide effectivesupport for the analysis of wave erosion on the bank slope in the water-level-fluctuating zone ofthe Three Gorges Reservoir area.